Five‐year outcomes from a prospective comparative effectiveness study evaluating external‐beam radiotherapy with or without low‐dose‐rate brachytherapy boost for localized prostate cancer. Issue 11 (17th February 2021) - Pasalic, Dario; Barocas, Daniel A.; Huang, Li‐Ching; Zhao, Zhiguo; Koyama, Tatsuki; Tang, Chad; Conwill, Ralph; Goodman, Michael; Hamilton, Ann S.; Wu, Xiao‐Cheng; Paddock, Lisa E.; Stroup, Antoinette M.; et al.
Abstract : Background: To inform patients who are in the process of selecting prostate cancer treatment, the authors compared disease‐specific function after external‐beam radiotherapy (EBRT) alone versus EBRT plus a low‐dose‐rate (LDR) brachytherapy boost (EBRT‐LDR). Methods: For this prospective study, men who had localized prostate cancer in 2011 and 2012 were enrolled. Assessments at baseline, 0.5, 1, 3, and 5 years included the patient‐reported Expanded Prostate Index Composite, the 36‐item Medical Outcomes Study Short‐Form Health Survey, and treatment‐related regret. Regression models were adjusted for baseline function and for patient and treatment characteristics. The minimum clinically important difference in scores on the Expanded Prostate Index Composite 26‐item instrument was from 5 to 7 for urinary irritation and from 4 to 6 for bowel function. Results: Six‐hundred ninety‐five men met inclusion criteria and received either EBRT (n = 583) or EBRT‐LDR (n = 112). Patients in the EBRT‐LDR group were younger (median age, 66 years [interquartile range [IQR], 60‐71 years] vs 69 years [IQR, 64‐74 years]; P < .001), were less likely to receive pelvic radiotherapy (10% vs 18%; P = .040), and had higher baseline 36‐item Medical Outcomes Study Short‐Form Health Survey physical function scores (median score, 95 [IQR, 86‐100] vs 90 [IQR, 70‐100]; P < .001). Over a 3‐year period, compared with EBRT, EBRT‐LDR was associated with worse urinary irritative scores (adjusted mean difference at 3 years, −5.4; 95% CI, −9.3, −1.6) and bowel function scores (−4.1; 95% CI, −7.6, −0.5). The differences were no longer clinically meaningful at 5 years (difference in urinary irritative scores: −4.5; 95% CI, −8.4, −0.5; difference in bowel function scores: −2.1; 95% CI, −5.7, −1.4). However, men who received EBRT‐LDR were more likely to report moderate or big problems with urinary function bother (adjusted odds ratio, 3.5; 95% CI, 1.5‐8.2) and frequent urination (adjusted odds ratio, 2.6; 95% CI, 1.2‐5.6) through 5 years. There were no differences in survival or treatment‐related regret between treatment groups. Conclusions: Compared with EBRT alone, EBRT‐LDR was associated with clinically meaningful worse urinary irritative and bowel function over 3 years after treatment and more urinary bother at 5 years. Lay Summary: In men with prostate cancer who received external‐beam radiation therapy (EBRT) with or without a brachytherapy boost (EBRT‐LDR), EBRT‐LDR was associated with clinically worse urinary irritation and bowel function through 3 years but resolved after 5 years. Men who received EBRT‐LDR continued to report moderate‐to‐big problems with urinary function bother and frequent urination through 5 years. There was no difference in treatment‐related regret or survival between patients who received EBRT and those who received EBRT‐LDR. These intermediate‐term estimates of function may facilitate counseling for men who are selecting treatment. Abstract : Among men with prostate cancer who receive external‐beam radiation therapy with or without brachytherapy boost, a clinically worse decline in urinary irritation and bowel function is observed through 3 years in the brachytherapy group. Through 5 years, these symptoms are no longer clinically meaningful; however, patients in the brachytherapy group continue to report moderate‐to‐large problems with urinary function bother and frequent urination.